Ultrastructural pathology of human peritumoural oedematous cerebellar cortex - Castejón, Orlando José (Folia Neuropathologica, 2016)
Cerebellar cortical biopsies of the peritumoural region of seven patients with cerebellar haemangioma, mesencephalic meningioma, cerebellopontine astrocytoma, cerebellopontine meningioma, and medulloblastoma of cerebellar vermis were examined by means of conventional transmission electron microscopy. Granule cells showed oedematous cytoplasm and mitochondria. Swollen Golgi cells exhibited lipofuscin granules and intranuclear inclusions. Both neuron cell types displayed swollen dendritic digits synapsing with afferent mossy fibre endings. Degenerated myelinated axons corresponding to afferent mossy and climbing fibres and efferent Purkinje cell axons were observed at the granular layer. Dense and clear ischaemic Purkinje cells established degenerated synapses with swollen parallel fibre synaptic varicosities. Degenerated Purkinje cell recurrent axonal collaterals were found at the molecular layer. Swollen and clear Bergmann glial cell cytoplasm was observed closely applied to the oedematous clear and dark Purkinje cell body, dendritic trunk, secondary and tertiary dendritic branches. Swollen climbing fibre endings featured by numerous microtubules and neurofilaments, and a decreased number of synaptic vesicles were observed making degenerated axo-spinodendritic synapses with clear and swollen dendritic spines from Purkinje, Golgi, basket and stellate cell dendrites. Swollen stellate neurons showed oedematous mitochondria. Lipofuscin-rich astrocytes and reactive phagocytic astrocytes were observed. The latter appeared engulfing haematogenous proteinaceous oedema fluid. All cerebellar neurons showed stress endoplasmic reticulum dysfunction featured by focal dilated cisterns and detachment of associated ribosomes. Myelin sheath degeneration was related with oligodendrocyte degenerating hydropic changes. The peritumoural ischaemic cerebellar nerve and glial cell abnormalities were related with neurobehavioral changes, tremor, nystagmus, dismetry and gait disturbance observed in the patients examined. The ultrastructural pathological changes were correlated with the biochemical cascade induced by vasogenic and cytotoxic oedema, altered calcium homeostasis, increased glutamate excitotoxicity, oxidative stress and DNA damage.